Biobanking potential for biomedical research in endocrinology - K. A. Chubakova; E. M. Kamenskikh; Yu. O. Bakhareva; T. V. Saprina (Кардиоваскулярная терапия и профилактика)
Biobanking is an actively developing scientific area that provides tools for conducting biomedical research, increasing the reliability and reproducibility of their results. In endocrinology, more and more attention is paid to the study of molecular and genetic markers of diseases for the selection of new points of influence in treatment, the development of targeted therapy and a strategy for personalized prevention. This approach is designed to solve the problems of endocrine disorders, their complications, causing significant damage to the individual and he population health, and reduce the financial burden of chronic endocrine disorders. To increase the reliability and reproducibility of research results, requirements for working with biological material should be strictly complied. The use of biobanking will increase the validity of data obtained in clinical trials in endocrinology. There are successful examples of Russian and foreign studies using the capabilities of biobanks aimed at studying diabetes, polycystic ovary syndrome, adenomas and other endocrine disorders. The article discusses the prospects for partnership with biobanks in the framework of endocrinology research. The purpose of this review is to analyze the literature to systematize knowledge for application of biobanking in biomedical research in the field of endocrinology.